VD_FINDINFO Jug / 2017 / 413 vom 12. Juli 2017 - VD Tribunal cantonal (2017)
RECEL, ADMINISTRATION DES PREUVES, REJET DE LA DEMANDE | 160 CP, 46 al. 2 CP, 147 CPP (CH), 159 CPP (CH), 429 al. 1 let. a CPP (CH), 429 CPP (CH)